The good girl (MIRA Books, Mira Books, Blackstone Publishing, 2014)
The daughter of a prominent Chicago judge and his socialite wife, inner-city art teacher Mia Dennett is taken hostage by her one-night stand, Colin Thatcher, who, instead of delivering her to his employers, hides her in a secluded cabin in rural Minnesota to keep her safe from harm.

Pretty baby (Thorndike Press large print peer picks, ,, 2015)
She sees the teenage girl on the train platform, standing in the pouring rain, clutching an infant in her arms. She boards a train and is whisked away. But she can't get the girl out of her head... Heidi Wood has always been a charitable woman: she works for a nonprofit, takes in stray cats. Still, her husband and daughter are horrified when Heidi returns home one day with a young woman named Willow and her four-month-old baby in tow. Disheveled and apparently homeless, this girl could be a criminal--or worse. But despite her family's objections, Heidi invites Willow and the baby to take refuge in their home. Heidi spends the next few days helping Willow get back on her feet, but as clues into Willow's past begin to surface, Heidi is forced to decide how far she's willing to go to help a stranger. What starts as an act of kindness quickly spirals into a story far more twisted than anyone could have anticipated. Don't miss this thrilling follow-up to The Good Girl.